PENGARUH KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN PELANGGAN QUDWAH MART DI LEBAK - Albadiah, Ilmi; Syukur, Mahmudin (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2022)
Qudwah Mart is a minimarket brand that sells daily necessities such as food, drinks, stationery, and others.The formulation of the problem in this study is, first, how is Qudwah Mart's service quality, and second, how is the effect of service quality on customer satisfaction. While the objectives in this study are, firstly to determine the quality of service, the second to determine the effect of service quality on customer satisfaction. The method used is a quantitative method. Correlational quantitative method is research that aims to determine the effect or relationship between two or more variables. The population in this study amounted to 347 students while the samples taken were 52 students from the total population. The conclusion in this study is that the services provided so far to customers must always be improved so that customers are more satisfied and believe, Qudwah Mart Customer Satisfaction will be created if customers are satisfied with the products and services received. The results based on the (t test) show that service quality has a significant effect on customer satisfaction with the correlation value t count > t table (t count 9.387 is greater than the value t table = 2.008). The coefficient of determination test results obtained R Square of 0.638, which means that 63.8% of customer satisfaction is influenced by the service quality variable. The remaining 36.2% is explained by other variables. Keywords: Service Quality and Customer Satisfaction